(untitled) (Altre Modernità, 2018)
An author of best-sellers, the most successful of which is an autobiography focused on her mother who committed suicide, Delphine de Vigan has only partially obtained recognition for her work, even if her latest novel, D’après une histoire vraie (2015), has been awarded by the Renaudot, one of the literary prizes that are authentic cultural institutions in France (v. Bourdieu, Ducas). The article analyzes the novel, whose plot, explicitly inspired by Stephen King, staged a writer and her doppelgänger, who is a ghost writer by profession. Through the examination of the way the characters have been shaped, the article investigates how the writer, behind the subterfuge of a fake autobiography and an unreliable narrator, ponders about the author’s identity and suggests, in a hidden strategy, how to be positioned in the French literary field and establishment.